Proactive Stakeholder Management: A Case Study of a Major Pharmaceutical Corporation - Ali, Mohammad A. (Journal of Management Policy and Practice, 2017)
This study tries to explore the efficacy of stakeholder management. This study seeks to offer a comprehensive understanding of the benefits of stakeholder management and as a qualitative work focuses on building theoretical generalizations. The study consists of one primary and one secondary case study. The findings suggest that stakeholder organizations use stakeholder management as a differentiator from their competitors and benefit in terms of customer loyalty; employee loyalty and pride; positive reputation and goodwill; capacity for better decisions; and organizational flexibility. Finally, this work suggests that the Achilles’ heel of stakeholder management is its complicated nature.